O estudo diário do violino: uma investigação da rotina de preparação técnico-interpretativa dos alunos do curso de bacharelado em música da FAMES - Silas de Andrade Neto (2010)
To know how to practice is an indispensable tool for the instrumentalist. The well done daily practice leads to a secure, comfortable, efficient performance, which consequently gives satisfaction to the musician. From the hypothesis that most of the undergraduate students do not know how to prepare properly to their tests and recitals, we investigated the technical and interpretative practice routine of undergraduate violin students of FAMES Espírito Santo Music School. Then we compared the results of this investigation to whatare the practicing strategies recommended by four of the most important names of violin pedagogy FLESCH, GALAMIAN, GERLE and GREEN. This way we tried to find out if there are any flaws in the way these students prepare themselves to their tests and recitals.